(untitled) (Annals of Medical Research, 2021)
Aim: We assessed the safety and efficacy of three different local anesthesia methods (pudendal nerve blockade, tenoxicam suppository and rectal lidocaine gel) before transrectal ultrasound (TRUS)-guided biopsy of the prostate in this study.